The Effects of Episodic Versus Continuous and Major Versus Mild Depression and Anxiety Symptoms on Pregnancy and Labour Complications - Laura Schwartz; Angela Bowen; Nazeem Muhajarine (Archives of Depression and Anxiety - Peertechz Publications, 2015)
Background:   Depression  occurs  in  approximately  20%  of  pregnant  women,  with  up  to  25% experiencing  anxiety.  Various  pregnancy  and  labour  complications  have  been  associated  with maternal mood problems. Methods:  This population study of antenatal and early postpartum depression and maternal, child outcomes involved 649 women assessed three times: the second trimester, the third trimester, and in the early postpartum. Our objective was to determine the occurrence and outcomes on pregnancy and labour of major and mild depression. Results:  Major depression in the second trimester was significantly associated with developing gestational  diabetes  and  swelling/edema.  Major  depression  that  occurred  continuously  throughout pregnancy  was  significantly  associated  with  induced  labour  and  antenatal  bleeding/abruption.  Mild  depression  in  the  second  trimester  was  significantly  associated  with  antenatal  bleeding/abruption and premature rupture of the membranes. Mild depression in the third trimester was associated with caesarean birth. Mild depression that occurred continuously throughout pregnancy was significantly associated with the use of vacuum/forceps or operative delivery. Conclusions: Our  findings  show  that  either  episodic  depression  or  mild  depression  can  have significant negative impact on pregnancy and labour complications.